2020
DOI: 10.25081/josac.2020.v29.i1.6330
|View full text |Cite
|
Sign up to set email alerts
|

Biorational strategies for the management of insect pests of spice crops

Abstract: Pest control strategies based on relatively non-toxic procedures that preserve the health of the ecosystem and minimizes negative effects on beneficial organisms, and utilize microbial pathogens and their products, plant natural products, semiochemicals, biotechnological strategies and reduced-risk pesticides can be termed as ‘biorational strategies’. This review consolidates the information available on the use of biorational strategies for the management of insect pests of spice crops such as Piper n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…(Gaur 1990). The application of P. lilacinum in combination with neem cake improved nematode control, plant growth and yield in nematode infested cardamom plantations (Ali, 1987;NRCS, 1993;Eapen and Venugopal, 1995;Mathew, 2007;Devasahayam et al, 2015). Sheela (2007) found that P. lilacinum reduced root knot nematodes by 48.5 to 57% in pot culture studies and by 19.7% in field studies.…”
Section: Discussionmentioning
confidence: 99%
“…(Gaur 1990). The application of P. lilacinum in combination with neem cake improved nematode control, plant growth and yield in nematode infested cardamom plantations (Ali, 1987;NRCS, 1993;Eapen and Venugopal, 1995;Mathew, 2007;Devasahayam et al, 2015). Sheela (2007) found that P. lilacinum reduced root knot nematodes by 48.5 to 57% in pot culture studies and by 19.7% in field studies.…”
Section: Discussionmentioning
confidence: 99%
“…Young trees require pruning to develop 3-5 well-spaced branches into the main scaffold structure. Regular pruning rejuvenates fruiting wood and regulates tree size in closely planted orchards [71].…”
Section: Pruning and Trainingmentioning
confidence: 99%
“…Maturity index: Flesh color varies from green to brown, dark brown, red, or black, depending on variety [71]. At maturity, exocarp hardens and separates from pulp.…”
Section: Crop Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium oxysporum attacks the crop in the field and also during storage . Earlier, synthetic fungicides were used extensively to reduce crop loss, but as the crop had good export value, levels of chemical residues were kept low in accordance with the standards set by the importing countries …”
Section: Introductionmentioning
confidence: 99%